Geografski informacijski sistemi v Sloveniji 2011–2012 (GIS v Sloveniji, 2012)
This is the eleventh volume (‘Geographic information systems in Slovenia, 2011–2012’) in the collection, consisting of twenty-seven articles discussing the use of geographic information systems in geography, geodesy, cartography, geology, natural disasters, protection of natural and cultural heritage, and business.